CEU Opening Ceremony 2003
Recording of the official opening ceremony of the 13th academic year at CEU which took place on Friday, September 26, 2003 at Vigadó Concert Hall in Budapest. The welcome address is delivered by the Master of Ceremonies and Academic Pro-Rector László Mátyás. He then introduces President and Rector of CEU, Yehuda Elkana who delivers the opening remarks. Further welcoming remarks are then provided by Karl Hall, Assistant Professor at the Department of History. Dóra Benedek (Second year, Department of Economics, 2004) is welcoming the incoming students. The response comes from incoming student Ales Vidmar (Department of Political Science, 2004). After the musical interlude in which Charity Tillemann-Dick (vocal) and Lela Purtskhvanidze (Department of Gender Studies, 2004, piano) perform George Gershwin “Summertime” and Claude Debussy’ “Nuit d’étoile,” Yehuda Elkana introduces the keynote speaker. The opening address is then delivered by keynote speaker István Csillag, Hungarian Minister of Economics and Transport who speaks about “Hungarian Economic Policy on the Threshold of EU Accession.” Another musical moment follows the opening address, in which Charity Tillemann-Dick (vocal) and Mariann Rigó (Second year, Department of Economics, 2004, piano) perform Charles Gounod, “Ah! Je veux vivre.” The ceremony ends with László Mátyás’ concluding remarks.